The role of LSWS (satellite traces) and low latitude Esb layers in causing the variability of ESF irregularities over Indian sector - Sreekumar, Sreeba; Sripathi, S. (My University, 2018)
We investigate the ionogram signatures of LSWS (satellite traces) and low latitude Esb layers as a basis for causing variabilities of ESF irregularities in addition to post sunset vertical drift using ground based ionosondes located at Tirunelveli (8.71 N, 77.75 E, Geomag. Lat 0.21 N) and Hyderabad (17.38 N, 78.48 E, Geomag. Lat 8.74 N) for the year 2015. Results show, statistically, that the presence/ absence of STs are higher/lower than the absence/presence of Esb prior to occurrence/non-occurrence of ESF during all the seasons. This implies the importance of ST/LSWS in the ESF occurrence. Results of weak correlation of low latitude Esb layers with ESF possibly indicate its coupling to higher apex altitude than base of the F-layer. Significant equinoctial asymmetry is also observed in both the ESF and ST occurrences wherein vernal is dominant than autumn equinox. Band-pass filtered h’F oscillations of 1–1.5 h reveal significant wave amplification during the PRE on ESF than non-ESF days and also during vernal than autumn equinox. Further investigations suggest that the height oscillations of early ESF and delayed ESF are amplified according to their onset time of ESF. The study suggests that post-sunset height rise of F-layer together with the presence of LSWS provide suitable conditions for the ESF development. Further, the presence of downward phase propagation on ESF days than other days indicate the presence of upward propagating Gravity Waves in the initiation of these wave structures
Keywords: ESF irregularities; Large scale wave structures; Ionosonde spread F; Esb layers; Equinoctial asymmetry of ESF irregularities